2018
DOI: 10.15296/ijwhr.2018.71
|View full text |Cite
|
Sign up to set email alerts
|

Desire and Attitude to Marriage Among Unmarried Iranian Youth: A Qualitative Study

Abstract: Introduction Marriage is the most common custom in all societies, which is recognized as the most important and fundamental form of communication and intimate affiliation (1). From William Good's perspective, the global revolution and the process of modernization, as well as social factors affect the family, marriage, and individuals (2). Over the past decades, due to cultural and social transformations, including urbanization and globalization, significant changes have occurred in the process of marriage thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this regard, the financial status and the high economic price of bearing children were the most critical factors. The results revealed that the unfavorable economic conditions changed the childbearing patterns and behaviors and decreased fertility ideals (Haerimehrizi et al, 2017;Keshavarz et al, 2018;Oshrieh et al, 2020;Zhang, 2018;Zhou, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the financial status and the high economic price of bearing children were the most critical factors. The results revealed that the unfavorable economic conditions changed the childbearing patterns and behaviors and decreased fertility ideals (Haerimehrizi et al, 2017;Keshavarz et al, 2018;Oshrieh et al, 2020;Zhang, 2018;Zhou, 2019).…”
Section: Discussionmentioning
confidence: 99%